The roles of the mtDNA-cGAS-STING axis in tumor immunity: from immune activation to immune evasion - Huang, Nan; Liu, Zheng; Lei, Haibo; Liu, Xiang (Frontiers in Immunology, 2026)
In the tumor microenvironment (TME), stress-induced mitochondrial DNA (mtDNA) leakage activates the mtDNA-cyclic GMP-AMP synthase (cGAS)- stimulator of interferon genes (STING) axis, which exerts a “double-edged sword” role in tumor immunity. On the one hand, it activates the STING- interferon regulatory factor 3 (IRF3) pathway via cyclic GMP-AMP (cGAMP) synthesis by cGAS, induces type I interferons (IFN-I), enhances the cytotoxic functions of CD8+ T cells and natural killer (NK) cells as well as the antigen-presenting capacity of dendritic cells (DCs), and also promotes M1 macrophage polarization and neutrophil extracellular trap (NETs) formation, thereby driving immune activation. On the other hand, sustained activation of this axis can induce programmed cell death ligand 1 (PD-L1) expression, recruit myeloid-derived suppressor cells (MDSCs), and cause T cells exhaustion, facilitating tumor immune evasion. Targeting mtDNA stability, constructing nano-drug delivery systems, or combining with immune checkpoint blockade can reshape the tumor immune microenvironment and provide new ideas for precision immunotherapy. This article systematically summarizes the dual effects of this axis on the tumor immune microenvironment, which not only deepens the understanding of cancer immunology but also provides guidance for the research, development, and optimization of precision tumor immunotherapies, and is expected to improve patient prognosis.